2016
DOI: 10.4103/2249-4863.184635
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study between platelet count, leukocyte count, nonhemorrhagic complications, and duration of hospital stay in dengue fever with thrombocytopenia

Abstract: Introduction:Dengue is one of the common diseases presenting as fever with thrombocytopenia, also causing significant morbidity and complications.Objectives:Though the correlation between platelet count, bleeding manifestations and hemorrhagic complications has been extensively studied, less is known about the correlation between platelet count and non hemorrhagic complications. This study was done to see the correlation between platelet count and non hemorrhagic complications, duration of hospital stay and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 7 publications
4
25
0
1
Order By: Relevance
“…23,24 A few studies had a lower and others, a higher proportion of cases with leucopenia. 1,2,4,15,16,18,25 A normal leucocyte count was observed in 55% of cases in our study in concordance with few studies but it was lower and higher in other studies. 2,4,15,18,21,24 Leucocytosis was noted in 9% of cases in our study in concordance with few studies.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…23,24 A few studies had a lower and others, a higher proportion of cases with leucopenia. 1,2,4,15,16,18,25 A normal leucocyte count was observed in 55% of cases in our study in concordance with few studies but it was lower and higher in other studies. 2,4,15,18,21,24 Leucocytosis was noted in 9% of cases in our study in concordance with few studies.…”
Section: Discussionsupporting
confidence: 77%
“…16,17 In their study Juan Carlos et al have observed that leucopenia is accompanied by a sudden drop in platelet count preceding plasma leakage. Our study suggests that leucopenia could be a marker of severe dengue as over half (52%) of the cases are associated with severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations